Listeria monocytogenes interferes with host cell mitosis through its virulence factors InlC and ActA - Costa, AC (2020)
Listeria monocytogenes is among the best-characterized intracellular pathogens. Its virulence factors, and thewaythey interfere with host cells to hijack host functions and promote the establishment and dissemination of the infection, have been the focus of multiple studies over the last 30 years. During cellular infection, L. monocytogenes was shown to induce host DNA damage and delay the host cell cycle to its own benefit. However, whether the cell cycle stage would interfere with the capacity of Listeria to infect human cultured cell lines was never assessed. We found here that L. monocytogenes preferentially infects cultured cells in G2/M phases. Inside G2/M cells, the bacteria lead to an increase in the overall mitosis duration by delaying the mitotic exit. We showed that L. monocytogenes infection causes a sustained activation of the spindle assembly checkpoint, which we correlated with the increase in the percentage of misaligned chromosomes detected in infected cells. Moreover, we demonstrated that chromosome misalignment in Listeria-infected cells required the function of two Listeria virulence factors, ActA and InlC. Our findings show the pleiotropic role of Listeria virulence factors and their cooperative action in successfully establishing the cellular infection.